A cultura informacional e participativa de fãs: análise da rede e processo de criação - Georgia Geogletti Cordeiro Dantas (2015)
In contemporary society much time is devoted to leisure activities. However, the information has an important role to play in this context. Thus, it is relevant to the Information Science the understanding of informational culture of specialized communities, as is the case of fandoms, and investigate how the dynamics of these environments influence the informational culture of the fans. The aim of this study was to identify, to organize and to analyze the information culture and the production of produsers fans through the participatory culture of fandoms, and the multimedia production arising from them, in order to understand the formation of the contemporary informational subject on the network. The research was based on concepts such as participatory culture, information culture, fan, fandom, produsage, career progression,semiotics, intersemiotic translation, metatext and interpretation. The adopted methodology combined quantitative and qualitative methods with emphasis on elements of genetic criticism, social network analysis, interviews and non-participant observation. As a result, it was possible to observe that in the surveyed communities fans are mostly women with a good level of education who commonly devote time to cultural production in fandoms. Throughout the network creation process, these individuals interact and make negotiations of meanings with other fans. When they came across information needs to build their significance, the fans develop a series of actions that would become habitus and to consolidate into informational culture. Despite the endless repertoire of motivations that keep the fans producing, recurring trends were noticed. It was observed that the subjects of the research make different intersemiotic translations in their fan performances based on the original works and the prompts proposed and shared in fandoms. It was noticed that the informational culture of the fans is mobilized by multimedia and transmedia resources in the production and dissemination of its content. Fans expand and extrapolate the fandoms as they build complex symbolic systems. In this context, the participatory culture developed in fandoms allowed to contemplate the network, collaborative creation process and the establishment of informational culture among contemporary subjects immersed in the production ofinformation and meanings originally motivated by pleasure.